Shock induced endotheliopathy (SHINE) in acute critical illness - a unifying pathophysiologic mechanism - Johansson, PärIngemar (Crit Care, 2017)
One quarter of patients suffering from acute critical illness such as severe trauma, sepsis, myocardial infarction (MI) or post cardiac arrest syndrome (PCAS) develop severe hemostatic aberrations and coagulopathy, which are associated with excess mortality. Despite the different types of injurious “hit”, acutely critically ill patients share several phenotypic features that may be driven by the shock. This response, mounted by the body to various life-threatening conditions, is relatively homogenous and most likely evolutionarily adapted. We propose that shock-induced sympatho-adrenal hyperactivation is a critical driver of endothelial cell and glycocalyx damage (endotheliopathy) in acute critical illness, with the overall aim of ensuring organ perfusion through an injured microvasculature. We have investigated more than 3000 patients suffering from different types of acute critical illness (severe trauma, sepsis, MI and PCAS) and have found a potential unifying pathologic link between sympatho-adrenal hyperactivation, endotheliopathy, and poor outcome. We entitled this proposed disease entity, shock-induced endotheliopathy (SHINE). Here we review the literature and discuss the pathophysiology of SHINE.